The type of sport, but not sex, impacts body composition and metabolic response to a complete weight loss-weight regain episode in weight cycling athletes: results from the WAVE study - Bagot S.; Ramos I.; Miles-Chan J.; Dulloo A.; Hackney A. C.; Boirie Y.; Duclos M.; Thivel D.; Isacco L. (Applied Physiology, Nutrition, and Metabolism, 2025)
Athletes may engage in weight cycling—successive episodes of weight loss and weight (re)gain—for performance reasons, but risk metabolic adaptations and regaining more fat that was lost (fat overshoot). This study aimed to assess the influence of a complete weight cycling episode on body composition, thermoregulation, and metabolism in athletes, considering sex and the type of sport practiced. Forty-eight athletes (28 males, 20 females) engaged in combat (n = 23), strength (n = 12), or endurance (n = 13) sports were examined under three experimental conditions (weight maintenance, weight loss, weight (re)gain) during a weight cycling episode using their habitual strategies. Body composition (dual-energy X-ray absorptiometry), core body temperature (telemetric temperature sensor), energy expenditure and substrate oxidation at rest and during moderate exercise (indirect calorimetry), and energy intake (48 h food record) were assessed. Overall, athletes lost 4.4 ± 2.3% body weight, 12.2 ± 10.6% fat mass, and 2.6 ± 2.3% fat-free mass (p < 0.001). All variables returned to baseline values during the regain period, and a higher fat mass regain was observed in endurance than combat athletes (p < 0.01). During weight loss, a transient increase in lipid and decrease in carbohydrate oxidation occurred at rest and during exercise (p < 0.001). Energy expenditure and core body temperature remained unchanged across the three experimental conditions, and no specific sex effect was observed. Overall, no apparent body weight nor fat overshoot was observed in athletes after a complete weight cycling episode. Nonetheless, the greater fat mass gain in endurance, compared with combat athletes, highlights a need for further specific long-term studies in this population.